Social attitudes toward Tongqi among the general public and associated determinants: a mixed-methods study in Hubei Province, China - Yang, Fen; Qiu, Yufei; Yue, Yake; Tong, Mengjie; Liu, Jiali; Zeng, Lijuan; Gu, Juan; Yu, Yiqing (Frontiers in Psychiatry, 2025)
BackgroundIn China, “Tongqi” (wives of men who have sex with men) remain a socially marginalized group. Public awareness and understanding of Tongqi are limited. Misconceptions and stigma persist, potentially hindering their access to social support and equitable treatment. However, empirical research in China on the general public’s attitudes toward Tongqi and the factors shaping these views remains scarce. This study aimed to investigate the general public’s social attitudes toward Tongqi and the factors influencing these attitudes.MethodsAn explanatory sequential mixed-methods design was employed in Hubei Province, China, in 2024. The quantitative phase involved a structured survey of 587 participants, while the qualitative phase included in-depth interviews with 20 individuals from diverse social backgrounds. Quantitative data were analyzed using descriptive statistics, independent samples t-tests, one-way ANOVA and multiple linear regression. Qualitative data were thematically analyzed using NVivo 14.ResultsThe mean score of social attitudes toward Tongqi was 89.93 (SD = 16.60), indicating a moderately neutral stance. Social attitude scores were significantly associated with gender (β = 5.39, P < 0.001), education (β = 3.37, P < 0.05), marital status (β = -3.45, P < 0.001), occupational status (β = 3.99, P < 0.05), perceptions of the current social environment (β = -4.83, P < 0.001) and sexual orientation (β = 5.66, P < 0.01). Qualitative analysis revealed three key themes: (1) Cognitive aspect—awareness shaped by traditional and societal norms; (2) Affective aspect—public empathy and emotional orientation toward Tongqi; (3) Behavior aspect—expressed needs and public expectations for support mechanisms.ConclusionThe general public holds moderately neutral social attitudes toward Tongqi, influenced by multiple factors. Deep-rooted stigma, driven by conservative views on marriage and sexuality, continues to marginalize this group. Although emotional sympathy exists, the absence of public visibility and structural support limits meaningful social action. Future research should expand to diverse populations and sociocultural settings to inform targeted interventions. Multisectoral engagement is urgently needed to enhance awareness, reduce stigma, and establish comprehensive support systems for Tongqi.